2019
DOI: 10.1016/j.ijid.2019.05.015
|View full text |Cite
|
Sign up to set email alerts
|

Post-tuberculosis incidence of diabetes, myocardial infarction, and stroke: Retrospective cohort analysis of patients formerly treated for tuberculosis in Taiwan, 2002–2013

Abstract: Objectives:To estimate the incidence of diabetes, acute myocardial infarction (AMI), and stroke; and to determine factors associated with diabetes, AMI, and stroke incidence among patients previously treated for tuberculosis (TB) disease.Methods:A retrospective cohort study was conducted among non-pediatric TB patients registered in the Taiwan National Health Insurance Research Database (NHIRD) from 2002–2013. Diabetes, AMI, and stroke incidence were defined by International Classification of Diseases (ICD)-9 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 10 publications
0
20
0
Order By: Relevance
“…In another example, a retrospective study using primary care data from the UK reported that the incidence of diabetes was significantly higher among those who previously had TB disease (pulmonary or extra-pulmonary TB) compared to those without a history of TB (incidence rate ratio range 2.2–5.4) [72]. Lastly, a preliminary retrospective cohort study of patients with history of pulmonary or extrapulmonary TB from Taiwan reported that the incidence rate of diabetes was higher among patients previously treated for TB disease compared to Taiwan’s national diabetes incidence estimates during a similar time period [73]. …”
Section: Section 4: Diabetes Incidence After Successful Tb Treatmentmentioning
confidence: 99%
“…In another example, a retrospective study using primary care data from the UK reported that the incidence of diabetes was significantly higher among those who previously had TB disease (pulmonary or extra-pulmonary TB) compared to those without a history of TB (incidence rate ratio range 2.2–5.4) [72]. Lastly, a preliminary retrospective cohort study of patients with history of pulmonary or extrapulmonary TB from Taiwan reported that the incidence rate of diabetes was higher among patients previously treated for TB disease compared to Taiwan’s national diabetes incidence estimates during a similar time period [73]. …”
Section: Section 4: Diabetes Incidence After Successful Tb Treatmentmentioning
confidence: 99%
“…Cause of death during treatment among people with TB and diabetes is not always clearly reported, but not only diabetes but also TB is associated with an increased risk of cardiovascular complications such as myocardial infarction [28,29] and stroke [30], possibly explaining the higher rate of deaths in the first few months of TB treatment in patients who also have diabetes [31,32]. Even after TB treatment success TB patients remain at increased mortality risk, possibly due to increased cardiovascular risk regardless of whether or not they have diabetes [28,33,34], although most studies have significant limitations (including limited follow-up time, lack of control of key confounders, or inappropriate selection of control series) [35]. [18][19][20]24,27] in text for evidence for and magnitude of possible relationships between diabetes and TB susceptibility, TB disease and prognosis).…”
Section: Effect Of Diabetes On Tb Disease Risk Presentation and Treatment Outcomesmentioning
confidence: 99%
“…In parallel, these regions account for almost 80% of global cardiovascular mortality 2 , 3 . Patients with TB, either active TB disease or latent TB infection, have an increased risk of developing atherosclerotic cardiovascular diseases (ASCVD), such as coronary artery disease (CAD) 4 6 , including acute myocardial infarction (AMI) 7 , 8 , and acute ischemic stroke 9 , 10 , as well as mortality due to these diseases 11 . However, the effect of pre-existing ASCVD on TB treatment outcomes is uncertain.…”
Section: Introductionmentioning
confidence: 99%